2021
DOI: 10.1111/ijcp.14188
|View full text |Cite
|
Sign up to set email alerts
|

Degree and duration of hypokalemia associated with peritonitis in patients undergoing peritoneal dialysis

Abstract: Background: Hypokalemia (LK) was associated with peritonitis in peritoneal dialysis (PD) patients, while the role of its degree and duration have not been fully established. Here, we conducted a retrospective cohort study to identify the relationships of LK degree and duration with peritonitis in PD patients.Methods: A total of 602 PD patients in our department from Jan 1st, 2009 to Dec 31st, 2019 entered the last analysis. Data were collected from their medical records.Serum potassium (SK) levels, degree of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…99 In addition to the degree of hypokalaemia, the duration of hypokalaemia was associated with the risk of peritonitis in PD patients. 100 Although there is no compelling evidence that treatment of hypokalaemia, constipation or gastroenteritis mitigates the risk of peritonitis, such problems, which are common in the PD setting, merit treatment in their own right. Based on previous observational and mechanistic studies of hypokalaemia in PD studies, the main contributory factor of hypokalaemia is low dietary potassium intake, rather than increased potassium excretion or intracellular shift.…”
Section: Prevention Of Peritonitismentioning
confidence: 99%
“…99 In addition to the degree of hypokalaemia, the duration of hypokalaemia was associated with the risk of peritonitis in PD patients. 100 Although there is no compelling evidence that treatment of hypokalaemia, constipation or gastroenteritis mitigates the risk of peritonitis, such problems, which are common in the PD setting, merit treatment in their own right. Based on previous observational and mechanistic studies of hypokalaemia in PD studies, the main contributory factor of hypokalaemia is low dietary potassium intake, rather than increased potassium excretion or intracellular shift.…”
Section: Prevention Of Peritonitismentioning
confidence: 99%
“…Electrolyte imbalance [25] is also commonly observed along with volume depletion and malnourishment due to peritonitis. Hypercalcemia [26], hypomagnesemia [25], hypokalemia [27,28], hypophosphatemia [29], and hypoalbuminemia [30] are also observed to occur in peritonitis patients and are key indices of frailty and sarcopenia. The bowel ileus caused by hypokalemia [31] may contribute to the overgrowth of intestinal microbiota [32], trigger bacterial penetration through the bowel wall, and cause repetitive peritonitis.…”
Section: Discussionmentioning
confidence: 99%
“…Ischemia, hypoxia, acidosis and inflammatory mediators collectively induce necrosis of epithelial cells, impair the intestinal mucosal barrier, increase intestinal permeability, and cause bacterial and endotoxin translocation [ 4 ]. Previous clinical studies have observed that PD patients with hypokalemia have a high prevalence of peritonitis [ 13 ]. The mechanisms for the increased risk of peritonitis caused by LK is speculated to be associated with malnutrition, impaired immune function and decreased intestinal motility [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hypokalemia, defined as potassium concentration < 3.5 mmol/l, affects 1–3% of the general population and patients with chronic kidney disease, and is more common (5–22%) among persons undergoing peritoneal dialysis (PD) [ 11 ], consequence of insufficient potassium intake and use of glucose dialysate. Peritonitis is a common and serious complication of PD [ 12 ] and patients with hypokalemia have a higher risk of PD-related peritonitis [ 13 ], but potential mechanisms for this phenomenon are not clear.…”
Section: Introductionmentioning
confidence: 99%